Body, science, and politics from the perspective of gender, sexuality, race, and class - Lole, Ana; Almeida, Carla Cristina (Argumentum, 2023)
This article explores the language around the body which aims to restrict it to the references of modern technoscience. It also aims to reveal the power relations that permeate knowledge about the body, highlighting its centrality in the social, political and subjective understanding of the world. A bibliographical study was carried out approaching social policies in the field of sexual and reproductive rights. It affirms that the body has been central to the strategies of power and moralisation of some segments of the population, particularly in regard of gender, sexualities, race, and class. The differences and inequalities of societal life are expressed through the body. Although the marks of social control can clearly be seen in modern capitalist society, we also seek to observe the potential of the body to alter the world, and to produce opposition and inventiveness. Keywords: Body. Gender. Race and Class. Social inequalities.